Implication of Tipping on Services (a case study on Restaurant and Hotel Services in Tasikmalaya) - Syafei , M Yani; Rahadi , Dedi Rianto; Sianturi, Gabriel (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Tipping in hotels and restaurants has become a custom in several countries. However, the outbreak of the Covid-19 pandemic raises questions regarding the willingness of customers to give tips in difficult times amid the spread of the Corona virus. Tipping is mandatory in some countries, although some countries prohibit tipping workers in fast food services and hotels. The purpose of this study is to determine the implication of tipping as a sign of appreciation given to workers of fast food restaurant and hotel who have provided satisfactory service. The method used in this study is a descriptive approach and a qualitative approach. The results show that tipping encourages workers to provide their best service to customers while at the same time motivating workers to give their best work performance. In addition, companies and workers can also find out whether customers are satisfied or dissatisfied while enjoying food at the fast food restaurant.